(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
The focus of this study is to show the relics used by the Ethiopian Orthodox Tewahedo Church (EOTC) in terms of religious folklore. Two churches from Addis Ababa Diocese and two churches from Arsi Diocese were selected for the study. The main purpose of the study was to analyze the scriptures from a religious point of view. The data was collected through observation, interviews, and documentary data collection methods. Sanctification means: They are the various properties or resources of the church in which the various spiritual and divine services of God are performed. While the rules governing the EOTC are the same, sometimes the written rules and regulations apply differently. The fact that the church written law is unenforceable and shows that religious folklore implements the practice without changing the rule formally. If the EOTC can create a way for the sacraments to be completely self-sufficient according to the canon, or if it is established that they are orthodox traditions and canons before they are used, it may be a solution to the conflict.